High‐Dose Donepezil (23 mg/day) for the Treatment of Moderate and Severe Alzheimer's Disease: Drug Profile and Clinical Guidelines - Cummings, Jeffrey L. (CNS Neurosci Ther, 2013)
To provide healthcare professionals with a comprehensive assessment of donepezil 23 mg and its role in treating Alzheimer's disease (AD), the Donepezil 23 mg Expert Working Group (EWG) convened in June 2011 to critically evaluate the clinical trial database for this higher dose formulation and the members' clinical experience with its use. Discussions were based on a large, 6‐month, phase 3 clinical trial in patients with moderate to severe AD that compared continuing donepezil 10 mg/day versus switching to 23 mg/day. In this trial, donepezil 23 mg/day demonstrated significantly greater cognitive benefits (mean change in Severe Impairment Battery score, 2.11 points; P < 0.001). Prespecified analyses showed that benefits were significant irrespective of concomitant memantine use. The EWG considered integrating these new data into clinical practice approaches. Dementia severity, tolerability of the 10 mg dose, and need for additional therapy were key selection criteria, as was monitoring of gastrointestinal side effects, as consideration of titration strategies is an important aspect of implementation. The EWG concluded that donepezil 23 mg is an efficacious therapy for moderate to severe AD, with or without concomitant memantine, extending the treatment opportunities available to manage moderate to severe AD dementia. EWG guidelines offer assistance to clinicians in choosing and implementing treatment options.